Weighted one-sided splicing systems - Yee, Sian Gang; Wan, Hen Fong; Sarmin, Nor Haniza; Turaev, Sherzod (2014)
Restrictions in splicing systems have been widely investigated in DNA computing in order to overcome the limitations of the generative power of splicing systems. In weighted splicing system, weights from the selected weighting spaces are used as one of the restrictions in splicing systems, which are associated to the axioms of the splicing systems. In this paper, weights from the selected weighting spaces are used as restriction to the axioms of one-sided splicing systems. Hence, a new variant of splicing system namely weighted one-sided splicing system is introduced. Next, the generative power of weighted one-sided splicing system is illustrated by some examples. In addition, generalization on the generative power of weighted one-sided splicing systems is also presented.